Measurement of jet production cross sections in deep-inelastic ep scattering at HERA - Andreev, Vladimir; Bolz, Arthur; Britzger, Daniel; Huber, Florian; Sauter, Michel David; Schöning, André (The European physical journal. C, Particles and fields, 2017)
A precision measurement of jet cross sections in neutral current deep-inelastic scattering for photon virtualities 5.5<Q2<80GeV25.5<Q2<80GeV25.5<Q^2 <80\,GeV^2 and inelasticities 0.2<y<0.60.2<y<0.60.2<y<0.6 is presented, using data taken with the H1 detector at HERA, corresponding to an integrated luminosity of 290pb−1290pb−1290\,pb^{-1}. Double-differential inclusive jet, dijet and trijet cross sections are measured simultaneously and are presented as a function of jet transverse momentum observables and as a function of Q2Q2Q^2. Jet cross sections normalised to the inclusive neutral current DIS cross section in the respective Q2Q2Q^2-interval are also determined. Previous results of inclusive jet cross sections in the range 150<Q2<15,000GeV2150<Q2<15,000GeV2150<Q^2 <15{,}000\,GeV^2 are extended to low transverse jet momenta 5<PjetT<7GeV5<PTjet<7GeV5<P_T^jet <7\,GeV . The data are compared to predictions from perturbative QCD in next-to-leading order in the strong coupling, in approximate next-to-next-to-leading order and in full next-to-next-to-leading order. Using also the recently published H1 jet data at high values of Q2Q2Q^2, the strong coupling constant αs(MZ)αs(MZ)α _s(M_Z) is determined in next-to-leading order.